2015
DOI: 10.1371/journal.pone.0144847
|View full text |Cite|
|
Sign up to set email alerts
|

Time-Dependent Progression of Demyelination and Axonal Pathology in MP4-Induced Experimental Autoimmune Encephalomyelitis

Abstract: BackgroundMultiple sclerosis (MS) is an autoimmune disease of the central nervous system (CNS) characterized by inflammation, demyelination and axonal pathology. Myelin basic protein/proteolipid protein (MBP-PLP) fusion protein MP4 is capable of inducing chronic experimental autoimmune encephalomyelitis (EAE) in susceptible mouse strains mirroring diverse histopathological and immunological hallmarks of MS. Limited availability of human tissue underscores the importance of animal models to study the pathology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The above data show that inflammatory responses and demyelination occur in MOG-induced EAE mice. However, previous studies have shown that remyelinated nerve fibers, which typically display thin and dense myelin lamellae by EM [4,36], are present in EAE. Thus, we subjected spinal cord samples obtained from MOG-injected mice under EM observation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above data show that inflammatory responses and demyelination occur in MOG-induced EAE mice. However, previous studies have shown that remyelinated nerve fibers, which typically display thin and dense myelin lamellae by EM [4,36], are present in EAE. Thus, we subjected spinal cord samples obtained from MOG-injected mice under EM observation.…”
Section: Resultsmentioning
confidence: 99%
“…Some patients with MS suffer from various progressive neurological deficits, whereas others occasionally experience improved neurological function during the course of the disease. In experimental autoimmune encephalomyelitis (EAE), both demyelination and remyelination coexist at the same time [4]. Thus, although remyelination is considered responsible for the improvement of clinical symptoms [5,6,7], a detailed mechanism by which remyelination occurs during MS remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…We are currently investigating the benefits of similar therapies, which target anti-inflammatory and remyelinating mechanisms, in the models utilized in this study as well as other translationally-relevant EAE models. Specifically, the PLP-induced model of RRMS that simulates multiple relapses ( 55 , 56 ), or a more severe and progressive model, such as that induced by MP4, a myelin basic protein-proteolipid protein fusion peptide ( 57 ) or MOG immunization in DBA/1 mice ( 36 , 58 , 59 ), will likely show more dramatic differences between monotherapies and dual therapy and allow us to discern more temporal effects. Even as promoting remyelination emerges as a viable and potentially symptom-reversing therapeutic strategy, immune modulation will remain critical and our study shows that tuftsin works effectively in combination with benztropine in two primary MS models.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism via which some patients experience neurological improvement remains unclear. However, increasing evidence shows that remyelination occurs in the MS/EAE [57][58][59][60]. In addition, recent studies showed that activated neural stem/progenitor cells around region sites contribute to remyelination [61,62].…”
Section: Nanotechnology and Msmentioning
confidence: 99%